Molecular model for hydrated biological tissues - Sato, Erika Tiemi; Rocha, Alexandre Reily [UNESP]; De Carvalho, Luis Felipe Das Chagas E Silva; Almeida, Janete Dias [UNESP]; Martinho, Herculano (American Physical Society (APS), 2015)
A density-functional microscopic model for soft tissues (STmod) is presented. The model was based on a prototype molecular structure from experimentally resolved type I collagen peptide residues and water clusters treated in periodic boundary conditions. We obtained the optimized geometry, binding and coupling energies, dipole moments, and vibrational frequencies. The results concerning the stability of the confined water clusters, the water-water, and water-collagen interactions were successfully correlated to some important experimental trends of normal and inflammatory tissues.